THE IMPACT OF CONCEPT MAPPING IN TEACHING SCIENCE IN MAGUINDANAO - Dalgan, Norma; Camua, Amour; Abellar, Melda; Tabulong, Analie; Unsi, Alibai (Advances in Social Sciences Research Journal, 2021)
Concept mapping is a teaching strategy that helps students to organize information and facts for knowledge representation. It can be used to help students understand science subject matters and concepts. The study sougth to determine the impact of the concept mapping in teaching science among Grade 12 students in Maguindanao. Specifically, this study aims to determine the students scores in a test before and after the introduction of concept mapping strategy. Likewise, the study determined the significant improvement of the students’ scores after the concept mapping strategy in instruction. The single group pretest-posttest design was used with a detailed lesson plan. The multiple choice type of test and consists of 25 items with lesson plan was the main tool for data gathering The mean, frequencey and percentage counts were used to describe the pretest and posttest scores of the students. The t-test was used to determine the significant difference between the students’ pretest and posttest scores. The t-value was set at 0.05 levels of significance. Findings from the study showed that there were significantly improve the scores of the pretest and posttest of the Grade 12 students in Maguindanao. This implies that the scores of the Grade 12 students improved significantly after the exposure of the concetp mapping strategy. This mean that use concetp mapping strategy increased the students’ scores.